ARCHAEOLOGICAL EVIDENCE IN CAMATA TAMBO, TAMBO INCA LOCATED IN UPPER MOQUEGUA VALLEY, ANDES SOUTH-CENTRAL - Chacaltana Cortez, Sofía (2010)
Archaeological excavations together with paleobotanical analyses conducted in qollqas (Inca storage rooms) at Camata Tambo, an Inca tambo (waystation) located 2,800 m.a.s.l in the upper Moquegua Valley of Southern Peru, suggest that these storage structures incorporated a sophisticated technology designed for storing and controlling multiple types of products from the Colesuyo region including local and distant coastal products. Apparently, this economic surplus based on foodstuffs was later distributed to nearby and far-away populations (e.g. in the altiplano). In addition, although Camata Tambo was in a ‘marginal’ locale of the empire, the site had important political economic functions in the area such as providing valley products to the emerging and more powerful altiplano elites. Further, data collected from excavations conducted at Camata Pueblo, a local community adjacent to the tambo (less than 100 meters), indicate that this community was greatly transformed by the close interactions with imperial infrastructure and bureaucracy that developed through Camata Tambo. The data presented indicate that waystations were institutions that not only provided food and lodging to imperial travelers, but which also had important political economic and administrative imperial roles. Finally, excavations suggest that the operation of these Inca institutions in marginal zones was more ambiguous and ‘open’ than in regions more directly controlled by the empire.